2006
DOI: 10.3200/jmbr.38.6.423-429
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Reachability in Single- and Multiple-Degree-of-Freedom Workspaces

Abstract: In comparisons of perceived (imagined) and actual reaches, investigators consistently find a tendency to overestimate. A primary explanation for that phenomenon is that individuals reach as a "whole-body engagement" involving multiple degrees of freedom (m-df). The authors examined right-handers (N = 28) in 1-df and m-df workspaces by having them judge the reachability of targets at midline, right, and left visual fields. Response profiles were similar for total error. Both conditions reflected an overestimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 15 publications
6
16
0
Order By: Relevance
“…Concerning the perceptual task, reachability judgments slightly overestimated actual action capabilities (23.8 mm on average, first block of trials), confirming the results obtained in previous studies (Bootsma et al, 1992;Carello et al, 1989;Coello & Iwanow, 2006;Fischer, 2000;Gabbard et al, 2006;Rochat & Wraga, 1997). In these studies, a tendency toward overestimation was reported-in particular, when estimates of reachability were provided in darkness or in the presence of postural constraints (as in the present study).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Concerning the perceptual task, reachability judgments slightly overestimated actual action capabilities (23.8 mm on average, first block of trials), confirming the results obtained in previous studies (Bootsma et al, 1992;Carello et al, 1989;Coello & Iwanow, 2006;Fischer, 2000;Gabbard et al, 2006;Rochat & Wraga, 1997). In these studies, a tendency toward overestimation was reported-in particular, when estimates of reachability were provided in darkness or in the presence of postural constraints (as in the present study).…”
Section: Discussionsupporting
confidence: 91%
“…Some previous data support this interpretation by showing that increasing uncertainty in a sensorimotor task affects perceptual judgments of object properties (Ernst & Banks, 2002), as well as perceptual learning (Barthelmé & Mamassian, 2009;Shibata, Yamagishi, Ishii, & Kawato, 2009). In the present experiment, the induced discrepancy between visual and motor-related information may then have been concurrently perceived as a sudden increase of the variability of the visuomotor system, resulting in a reduction of the confidence attributed to the sensorimotor anticipatory processes (Gabbard et al, 2006;Gabbard et al, 2005). Modifying the state of confidence may have subsequently influenced the perception of reachable space, inducing a conservative strategy when reachability estimates were provided.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The second key finding of children's overestimation supports previous studies showing that children in general overestimate in real time (e.g., Gabbard, Ammar, & Lee, 2006;Gabbard, Cacola, & Cordova, 2008, 2009a, 2009bGabbard, Cordova, & Ammar, 2007;Gabbard, Cordova, et al, 2009;Rochat, 1995;Schwebel & Plumert, 1999). Our mean bias data support this general observation and show that children, compared with adults, significantly overestimate as delay increases.…”
Section: Discussionsupporting
confidence: 91%